2020
DOI: 10.1038/s41598-020-64643-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-classifier prediction of knee osteoarthritis progression from incomplete imbalanced longitudinal data

Abstract: Conventional inclusion criteria used in osteoarthritis clinical trials are not very effective in selecting patients who would benefit from a therapy being tested. Typically majority of selected patients show no or limited disease progression during a trial period. As a consequence, the effect of the tested treatment cannot be observed, and the efforts and resources invested in running the trial are not rewarded. This could be avoided, if selection criteria were more predictive of the future disease progression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 34 publications
0
65
0
2
Order By: Relevance
“…X-ray combined with pain scores have been utilized by Halilaj et al to predict the progression of joint space narrowing (AUC = 0.86 using data from two visits spanning a year) and pain (AUC = 0.95 using data from a single visit) [6]. Similarly, another two studies (Tiulpin et al [10] and Widera et al [11]) made use of Xray images along with clinical data to predict KOA progression using either CNN or ML approaches achieving less accurate results. The current paper is the only one employing exclusively clinical non-imaging data and also contributes to the identification of important risk factors from a big pool of available features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray combined with pain scores have been utilized by Halilaj et al to predict the progression of joint space narrowing (AUC = 0.86 using data from two visits spanning a year) and pain (AUC = 0.95 using data from a single visit) [6]. Similarly, another two studies (Tiulpin et al [10] and Widera et al [11]) made use of Xray images along with clinical data to predict KOA progression using either CNN or ML approaches achieving less accurate results. The current paper is the only one employing exclusively clinical non-imaging data and also contributes to the identification of important risk factors from a big pool of available features.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that a knee X-ray image alone is already a very powerful source of data to predict whether a particular knee will have OA progression or not [10]. Futhermore, in the same year, Widera et al used several ML models (e.g., logistic regression, K-nearest neighbor, SVC (linear kernel), SVC (RBF kernel) and RF) in combination with clinical data and X-ray image assessment metrics to develop predictive models for patient selection that outperform the conventional inclusion criteria used in clinical trials [11]. However, few studies have tried to apply ML models for the prediction of KOA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging features seen on conventional radiography and magnetic resonance imaging (MRI) are another type of biomarker. Artificial intelligence and machine learning may be essential for identifying imaging biomarkers [11,17,18]. Widera and colleagues developed several machine learning-based models to predict disease progression using observational data from the European APPROACH consortium [17,19].…”
Section: Imaging and Machine Learningmentioning
confidence: 99%
“…Artificial intelligence and machine learning may be essential for identifying imaging biomarkers [11,17,18]. Widera and colleagues developed several machine learning-based models to predict disease progression using observational data from the European APPROACH consortium [17,19]. Models were validated using data from the Cohort Hip and Cohort Knee (CHECK) and Osteoarthritis Initiative (OAI) study populations.…”
Section: Imaging and Machine Learningmentioning
confidence: 99%